A graphene-based macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance and a preparation method thereof
By mixing graphene with boron-containing substances and sintering at high temperature, the problem of difficult graphene powder forming high-performance macroscopic materials is solved, and graphene-based macroscopic materials with high strength, ultra-high electromagnetic shielding and low friction wear coefficient are achieved Preparation, simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202311263818.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-09-27
AI Technical Summary
It is difficult to prepare high-performance graphene macroscopic materials in the prior art, and it is difficult to form high-strength and high electromagnetic shielding properties of graphene powders.
The graphene is uniformly mixed with boron-containing substances and sintered at high temperature. Boron acts as a graphitization catalyst and binder to promote graphitization, forming excellent mechanical properties, ultra-high conductivity, ultra-high electromagnetic shielding, low friction coefficient, and negative expansion. graphene-based macroscopic material.
Graphene-based macroscopic materials with high strength, ultra-high electromagnetic shielding performance, low friction and wear coefficient and negative expansion are achieved, which simplifies the preparation process and reduces costs.
Smart Images

Figure CN117416950B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of carbon-based materials, and specifically relates to a graphene-based macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance, and a preparation method of the graphene-based macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance. Background Art
[0002] Graphene is a two-dimensional carbon nanomaterial in which carbon atoms form a hexagonal honeycomb lattice in the form of sp2 hybridization. It has super high mechanical properties and super strong electrical conductivity. The high conductivity and broadband characteristics of graphene make it an ideal electromagnetic shielding material. In theory, the high conductivity of graphene allows it to effectively reflect electromagnetic waves. In addition, the two-dimensional structure of graphene can also provide effective electromagnetic shielding because electromagnetic waves are strongly scattered and absorbed when passing through the graphene layer. However, graphene as an electromagnetic shielding material is usually mainly powder, and graphene-based macroscopic materials (graphene films, graphene blocks) have been less studied as electromagnetic shielding materials.
[0003] At the same time, graphene has a low friction coefficient, a low thermal expansion coefficient, and even exhibits negative expansion within a certain temperature range. Therefore, it is expected that materials with excellent comprehensive performance can be obtained by compounding graphene into macroscopic materials (graphene films, graphene blocks).
[0004] The cost of preparing large-scale graphene thin film materials by chemical vapor deposition and other methods is also high. It is a better choice to prepare graphene macroscopic materials from powders, but small-scale graphene sheets are mainly connected by van der Waals forces, and the mechanical properties are poor. Therefore, the current state of graphene use is mainly powder, and it is very difficult to prepare high-performance large-scale macroscopic materials.
[0005] Yang Quanhong et al. (CN101993056A) mixed a graphene oxide aqueous solution and a polyvinyl alcohol solution, subjected them to a hydrothermal reaction for a certain period of time, freeze-dried them, and subjected them to a high-temperature heat treatment under an argon atmosphere to obtain a porous graphene block material. The graphene material prepared by this method has a developed pore structure, a large specific surface area, and poor mechanical properties.
[0006] Huang et al. (Materials and Design, 2020, 188) infiltrated TiO2 precursor into graphene oxide of different concentrations until saturation, then dried the prepared precursor in an oven at 70°C, and finally prepared graphene block material by vacuum sintering at 700°C. The study showed that the compressive strength of the material was only 20 MPa; under wet grinding conditions, the friction coefficient was as low as 0.13.
[0007] He et al. (ACS Nano 2021, 15, 2880-2892) first obtained graphene foam by freeze drying, then infiltrated phenolic resin / ethanol solution into the graphene foam, cured at 180°C for 3h, carbonized at 900°C for 1 hour, and then the obtained sample was infiltrated with polycarbosilane / xylene solution and heat treated at 1200°C. The above operations were repeated 12 times to obtain silicon carbide / graphene-based composite materials. The material exhibits excellent electromagnetic shielding performance. The average EMI electromagnetic shielding efficiency (SE) exceeds 70.2dB. However, the preparation process of this material is very complicated.
[0008] There is an urgent need for advanced high electromagnetic shielding materials in many fields. How to prepare high electromagnetic shielding and excellent comprehensive performance materials at low cost and high efficiency is a problem that needs to be solved urgently. Summary of the invention
[0009] The present invention aims to solve the technical problem that it is difficult to prepare high-performance graphene macroscopic materials using graphene powder as raw materials, and provides a macroscopic material with ultra-high electromagnetic shielding, low friction coefficient, and negative thermal expansion coefficient and a preparation method thereof.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0011] The purpose of the present invention is to provide a method for preparing a graphene-based material with ultra-high electromagnetic shielding and excellent comprehensive performance, which is specifically carried out according to the following steps: a boron-containing substance and graphene are uniformly mixed in a mass ratio of 0.001:1 to 0.3:1, and sintered at a high temperature to obtain the ultra-high electromagnetic shielding and excellent comprehensive performance macroscopic material.
[0012] It is further defined that the sintering is carried out at a temperature of 1400° C. to 2200° C. and a pressure of 0 MPa to 200 MPa for 10 ms to 15 days.
[0013] It is further defined that the thickness of graphene is 0.335 nm to 100 nm, and the size is 10 nm to 10000 nm.
[0014] It is further defined that the graphene can be one of mechanically exfoliated graphene, graphene oxide, reduced graphene oxide, CVD graphene, combustion synthesized graphene, etc., or a mixture of any ratio of several of them.
[0015] It is further defined that the method for preparing combustion synthesized graphene is carried out according to the methods described in [CN201210369707.0], [CN201210344115.3], and [CN201710638066.7].
[0016] Further defined, a preparation method of graphene powder is carried out according to the following steps: 1. Weigh 20% to 40% of magnesium powder and 60% to 80% of carbonate powder by mass percentage; wherein the purity of the magnesium powder is 95 to 99.999%, and the average particle diameter is 0.03 to 5 mm; the purity of the carbonate powder is 90 to 99.9%, and the average particle diameter is 0.01 to 5.2 mm; the carbonate is one of magnesium carbonate, calcium carbonate, and strontium carbonate, or a mixture of any proportion of the above; 2. Place the magnesium powder and carbonate powder weighed in step 1 into a ball mill for dry grinding Or wet grinding to obtain a mixed powder; wherein, the conditions for dry grinding are: grinding in an air atmosphere, a nitrogen atmosphere or an argon atmosphere, and the grinding time is 0.5 to 30 hours; the conditions for wet grinding are: in an air atmosphere, a nitrogen atmosphere or an argon atmosphere, with methanol, ethanol, propanol, butanol, isobutanol or acetone as the medium, grinding for 0.5 to 30 hours, then taking out, and drying in an air atmosphere, a nitrogen atmosphere, an argon atmosphere or under vacuum conditions, and the drying temperature is 30 to 90°C; 3. The mixed powder obtained in step 2 is subjected to a high pressure combustion synthesis reaction or a normal pressure combustion synthesis reaction to obtain graphene powder.
[0017] It is further defined that the boron substance is one of boron powder, boron oxide, boric acid, borate and organic borane, etc., or a mixture of any of them in any ratio.
[0018] It is further defined that the borate is one of borax, borax, etc. or a mixture of any proportions of any of them.
[0019] It is further defined that the organic borane is one of diborane, tetraborane, pentaborane, hexaborane and polycarborane or a mixture of any proportions thereof.
[0020] It is further defined that the mixing can be carried out by one or any combination of processes such as ball milling, homogeneous dispersion, mechanical stirring, ultrasonic stirring, mechanical grinding, etc.
[0021] It is further defined that the sintering equipment is one or any combination of spark plasma sintering, vacuum furnace, vacuum hot pressing sintering, hot isostatic pressing sintering equipment, laser 3D printing equipment, and gas protection furnace.
[0022] It is further defined that the sintering method is one of spark plasma sintering, vacuum hot pressing sintering, hot isostatic pressing sintering, vacuum furnace sintering, vacuum melting sintering, or any combination of several thereof.
[0023] A macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared by any of the above methods.
[0024] The present invention uniformly mixes graphene with boron-containing substances, and after high-temperature sintering, boron acts as a graphitization catalyst and binder to promote graphitization, thereby obtaining a graphene-based macroscopic material with excellent mechanical properties, ultra-high conductivity, ultra-high electromagnetic shielding, low friction coefficient, and negative expansion.
[0025] In the present invention, boron preferentially enters the turbostratic graphite structure by diffusion at high temperature, replaces carbon atoms, forms a hexagonal plane network, eliminates defects within or between layers in the turbostratic structure, forms larger grains, and accelerates the formation of the graphite structure. When the boron content is greater than 1.0wt%, boron carbide is formed. In high boron content, the boron dissolved in carbon reaches a saturated state, exceeds the solid solution limit, and boron precipitates out, occupies the interstitial position, and combines with carbon to form boron carbide. Boron carbide decomposes at high temperature, precipitates a crystallized graphite structure, and then uses this as a nucleus to further grow into larger crystals. The complete graphite crystal structure gives the material excellent electrical conductivity and ultra-high electromagnetic shielding performance.
[0026] On the other hand, the introduction of boron can act as a binder to strengthen graphene-based macroscopic materials (graphene films, graphene blocks). At the same time, the flake crystal structure of graphene gives it excellent lubrication properties. When friction occurs, a firm lubricating film can be formed to reduce the friction and wear coefficient of the material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] a. Prepare macroscopic graphene-based composite materials with high electromagnetic shielding and excellent comprehensive performance in a simple way.
[0029] b. The material has both functional and structural integration.
[0030] Taking Example 1 as an example, the friction and wear coefficient of the pure graphene block material under wet grinding conditions is 0.1. With the addition of boron, the friction and wear coefficient gradually decreases. When the mass fraction of boron is 20%, the friction and wear coefficient is 0.04.
[0031] The present invention can be widely used in electromagnetic shielding materials for mobile phones, Wi-Fi, precision electronics, aerospace equipment such as spacecraft and satellites, radars and military communication equipment.
[0032] Compared with existing graphene-based macroscopic materials, the material preparation method proposed in this patent is simple and highly operable, and is expected to be able to mass-produce graphene macroscopic materials.
[0033] The material exhibits high strength, ultra-high electromagnetic shielding performance, high conductivity, ultra-low friction and wear coefficient, and negative expansion. It realizes the structural and functional integration of graphene macro materials (graphene films, graphene blocks). It can be widely used in mobile phones, Wi-Fi, aerospace, electric vehicles, nuclear industry and other fields.
[0034] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 a is the XRD spectrum of the ultra-high electromagnetic shielding and excellent comprehensive performance macroscopic graphene-based composite material prepared in Example 1, b—Raman spectrum, c—fracture morphology, d—conductive properties, e—electromagnetic shielding properties, and f—compressive strength;
[0036] FIG2( a ) is a friction and wear curve of a macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared in Example 1;
[0037] Figure 2(b) is the thermal expansion coefficient of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared in Example 1. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0039] The following examples are provided to better understand the present invention, but the present invention is not limited to the contents described in the specific embodiments.
[0040] Example 1: The preparation method of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance in this embodiment is carried out according to the following steps:
[0041] The thickness of graphene is 5 to 8 layers, the average size is 2 μm, and the particle size of nano boron powder is 150 nm.
[0042] Weigh 95g of graphene powder and 5g of nano-boron powder, pour into 300g of ethanol solution, ultrasonicate for 60min, and stir at 1000 rpm for 120min to evenly disperse the graphene and boron powder; rotary evaporate at 60°C until the ethanol is completely evaporated, and collect the powder;
[0043] Under vacuum atmosphere, SPS sintering was used to prepare macroscopic graphene-based composite materials with ultra-high electromagnetic shielding and excellent comprehensive performance. The sintering temperature was 1600°C, the pressure was 40MPa, and the sintering time was 1min.
[0044] The conductivity was tested by the four-terminal method and was 453000 S·m -1 , using vector network analyzer to test its electromagnetic shielding performance EMI-SE TIt reaches 110dB (12-18GHz). Under wet grinding conditions, its friction and wear coefficient is only 0.06.
[0045] The XRD spectrum of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared in this embodiment is as follows: Figure 1 As shown, from Figure 1 It can be seen that the addition of boron promotes graphitization. After adding 5% boron powder, the conductivity of the material reaches 453000S·m -1 . The electromagnetic shielding performance reaches 110dB. The material exhibits excellent electrical conductivity and ultra-high electromagnetic shielding performance.
[0046] The friction and wear curve of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared in this embodiment is shown in FIG2. As can be seen from FIG2, after the introduction of boron, the friction and wear coefficient of the material decreases from 0.1 to 0.04. The material exhibits an ultra-low friction and wear coefficient. At the same time, the material exhibits negative expansion in a wide temperature range.
[0047] Table 1 Product performance at different ratios
[0048]
[0049]
[0050] As can be seen from Table 1, the product performance of this embodiment is the best.
[0051] Comparative example of embodiment 1:
[0052] Weigh 100 grams of graphene powder, pour it into 300g of ethanol solution, ultrasonicate for 60 minutes, and then stir at 1000 rpm for 120 minutes to evenly disperse the graphene in ethanol; rotary evaporate at 60°C until the ethanol is completely evaporated, and collect the powder; prepare graphene block material by SPS sintering under vacuum atmosphere, with a sintering temperature of 1600°C, a pressure of 40MPa, and a sintering time of 1min.
[0053] The conductivity was tested by the four-terminal method and was 353600 S·m -1 . Under wet grinding conditions, its friction and wear coefficient is 0.1.
[0054] Example 2: The preparation method of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance in this embodiment is carried out according to the following steps:
[0055] Weigh 10g of boron oxide, 90g of reduced graphene oxide, and put them into a zirconium oxide tank together with 300g of zirconium oxide balls (200g of 2mm zirconium oxide balls, 100g of 5mm zirconium oxide balls); add 300 parts of anhydrous ethanol, set the ball milling speed to 200 rpm, and set the ball milling time to 24h. After the ball milling is completed, place the slurry in a vacuum oven and dry it at 60°C until the ethanol is completely volatilized, then sieve out the zirconium oxide balls to obtain powder.
[0056] Then, vacuum hot pressing sintering is carried out at a temperature of 1800° C. and a pressure of 50 MPa for 30 minutes to obtain a graphene-based composite material.
[0057] The conductivity was tested by the four-terminal method and was 390000 S·m -1 , using vector network analyzer to test its electromagnetic shielding performance EMI-SE T Reached 102dB (12~18GHz).
[0058] Example 3: The preparation method of the macroscopic graphene-based composite material with ultra-high electromagnetic shielding and excellent comprehensive performance in this embodiment is carried out according to the following steps:
[0059] Weigh 30g polycarborane and 70g combustion synthesized graphene and add them to the homogenizer. Then add 600g anhydrous ethanol. The speed of the homogenizer is 400 rpm and the homogenization time is set to 4h. After completion, rotary evaporate at 60℃ until the ethanol is completely evaporated, collect the powder,
[0060] Macroscopic graphene-based composite materials with ultra-high electromagnetic shielding and excellent comprehensive performance are prepared by hot isostatic pressing and sintering. The hot isostatic pressing temperature is 2000°C, the pressure is 180MPa, and the sintering time is 30min.
[0061] The conductivity was tested by the four-terminal method and was 300000 S·m -1 , using vector network analyzer to test its electromagnetic shielding performance EMI-SE T It reaches 88dB (12-18GHz). Under wet grinding conditions, its friction and wear coefficient is only 0.12.
[0062] The graphene powder prepared by combustion synthesis used in this embodiment is prepared by the following steps:
[0063] 1. Weigh 30% magnesium powder and 70% calcium carbonate powder by mass percentage; wherein the purity of the magnesium powder is 99.5% and the average particle diameter is 0.1 mm; the purity of the calcium carbonate is 99% and the average particle diameter is 0.044 mm;
[0064] 2. Place the magnesium powder and calcium carbonate powder weighed in step 1 into a ball mill and dry grind in air for 1 hour to obtain a mixed powder;
[0065] 3. The mixed powder obtained in step 2 is subjected to a high pressure combustion synthesis reaction to obtain graphene powder.
[0066] The high pressure combustion synthesis reaction is carried out in the following steps:
[0067] a. Place the mixed powder obtained in step 2 in a general combustion synthesis reaction device with a pressure resistance of 1 to 5 MPa, and then add an ignition agent Fe3O4+Mg above the mixed powder;
[0068] b. Evacuate the interior of the combustion synthesis reaction device, then introduce 0.1 MPa of carbon dioxide into the combustion synthesis reaction device, and then seal the reaction device;
[0069] c. Use local electric heat ignition to pass 20A DC current through the spiral tungsten wire coil to ignite the ignition agent Fe3O4+Mg, so that the mixed powder undergoes combustion synthesis reaction;
[0070] d. After the combustion synthesis reaction is completed, cool to room temperature, take out the combustion reaction product, put it into 20% by mass hydrochloric acid for pickling, pickle it until the pH value of the pickling solution is less than 5, rinse it with distilled water until the rinse solution is neutral, and dry it in a vacuum to obtain graphene powder.
Claims
1. A method for preparing a graphene-based macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance, characterized in that: The preparation method is carried out according to the following steps: mixing the boron-containing substance and graphene uniformly at a ratio of 5% of the total mass of the boron-containing substance and the graphene, and sintering at high temperature to obtain an ultra-high conductive and ultra-high electromagnetic shielding macroscopic material, wherein the ultra-high conductive and ultra-high electromagnetic shielding macroscopic material is a graphene film or a graphene block; wherein the sintering is carried out at a temperature of 1400° C. to 2200° C. and a pressure of 40 MPa to 200 MPa for 10 ms to 15 days; The thickness of graphene is 5 to 8 layers, and the average size is 2 μm; The boron-containing substance is one or more of boron powder, boron oxide, boric acid, borate and organic borane.
2. The preparation method according to claim 1, characterized in that: The graphene is one or more of mechanically exfoliated graphene, oxidized graphene, reduced oxidized graphene, CVD graphene, and combustion synthesized graphene.
3. The preparation method according to claim 1, characterized in that: The borate is borax and / or borax; the organic borane is one or more of diborane, tetraborane, pentaborane, hexaborane and polycarborane.
4. The preparation method according to claim 1, characterized in that: Mixing can be carried out by one or more of ball milling, homogeneous dispersion, mechanical stirring, ultrasonic stirring, and mechanical grinding.
5. The preparation method according to claim 1, characterized in that: The sintering equipment is one or more of spark plasma sintering, vacuum furnace, vacuum hot pressing sintering, hot isostatic pressing sintering equipment, laser 3D printing equipment, and gas protection furnace.
6. The preparation method according to claim 1, characterized in that: The sintering method is one or more of spark plasma sintering, vacuum hot pressing sintering, hot isostatic pressing sintering, vacuum furnace sintering, and vacuum melting sintering.
7. A graphene-based macroscopic material with ultra-high electromagnetic shielding and excellent comprehensive performance prepared by the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Graphene-based porous macroscopic carbon material and preparation method thereof
CN101993056A
Method for preparing graphene powder by combustion synthesis
CN102826546A
Preparation method of graphene powder
CN102838110B
Preparation methods and applications of graphene synthesized from biomass combustion
CN109319765B
Boron-doped graphene
KR1020190035673A